Fusel yağı alkollerinden asetik esterlerin elde edilmesi sürecinde optimum çalışma şartlarının tesbiti - Yeğin, Salih Yüksel (Fen Bilimleri Enstitüsü, 1993)
Bu çalışmaya, Fusel Yağı, Özellikleri, oluşumu ve kullanıldığı yerler hakkında genel bilgiler verilerek başlanmış, bunu, yapısında ki maddeler ve bunların genel özelliklerini açıklayan bölüm izlemiş tir. Bu bölüm içinde, yapısındaki maddeleri bulurken kullanılan yön temler ve özellikleri de yer almaktadır. Daha sonra temel işlemlerden distilasyon ve genel özellikleri anlatılmış, distilasyon kullanılarak laboratuvar ve pilot ölçekte çeşitli çalışmalar teorik olarak yer almıştır. Burada ayrıca, Fusel Yağının bileşenlerine ayrılması için kullanılan farklı yöntemler de yer almıştır. Tezin, Fusel Yağı alkollerinin ayrıştın İmasında ikinci önemli aşaması ise, Asetik Asit ile esterleşme reaksiyonunun gerçekleştirilmesidir. Bu bölümde, yine temel işlemlerden esterleşme ve genel özellikleri açıklanmış, operasyon sonucu elde edilen esterlerin genel özellikleri verilmiş ve Fusel Yağının esterleşmesi anlatılmıştır. Son bölümde, yukarıda açıklanan teorik bölümün tamamı deneysel çalışmalar ile desteklenmiş, operasyonlar yapılırken çalışılan düzenek, operasyonun yapılması ve elde edilen numunelerin analizleri incelenmiş ve bu bilgiler tablo veya grafikler ile sunulmuştur. Ayrıca operasyon esnasında etkin olan parametreler tek tek irdelenerek etkileri ve miktarları tespit edilmiştir. Bulunan sonuçlara göre, çalışma hakkında genel yorumlar yapılmıştır.

As we approach to the 21 th century, environmental protection has become the most important subject to be studied for the human being. Numerious studies have been carried out on different aspects related to the environmen. The aim of these studies is to support and improve environmen and keep it clean. In this study it is armed to evaluate use fusel oil which is seen as an waste in economic and environmentally friendy way. It contains alcohols which may be esteri fied make it a valuable chemi cals. Studies were carried out in two stages. The first stage was a laboratory scale study and the second stage was a pilot plant scale study which was planned as pre-industrial scale application. The pilot plant studies were planned and organized in the light of results obtained from laboratory studies in which the amount of matterial to be used is determined and the possible product are estimated. Simi larly, the results of pilot plant studies are considered to consist a good base for the industrial scale production. In this frame, the study is consisted of seven major chapters. In the intoduction chapter, the topic and the its general properties are defined. In the second chapter, the raw materials and operations used for production of acetic esters are studied. The third chapter contains the detailed theoretical study of the properties of these raw materials and operations. In the fourth chapter, the experimental results are presented and the aspects theoretically studied in the previous chapter are supported by experimental results. The last chapter is consisted of the general evaluation of all study. The con tents of these chapter are summerized bellow. In the introduction chapter, the resons why this study needs to be carried out and the most important points considered in the study are briefly explained. Its aim is to briefly explain the subject and to give general information about the thesis. The second chapter of the thesis is about the properties of the viii fusel oil which is used as the raw material in the study. Firstly, the fusel oil is defined and its general physical and chemical pro perties are given. The formation of fusel oil and the major factors affecting its formation have been explained. The relation between the composition of fusel oil and starting raw material ant its origine (fermented product) Is determined. Then numerrous different areas where the fusel oil is used are individually reviewed. The next chapter begins with a section in which the conditions of fermentation and the composition of the fusel oil which consi- derbly varies have been studied. It's followed by the section in which the physical properties (open-closed formulas, molecular weight, boilig, point, melting point, density, refractive index, specific heat, viscosity, azeotropic property) of the alcohols con tained by fusel oil and their areas of use have been given. This chapter ends with a section which explains the analytical methods such as chromatography, colorometry, spectrometry, refractrometry which used in the studying of compositions of fusel oil and their principles. The fourth chapters, deals with the fractionation of the fusel oil into its components. Here, the distillation which is the most common method used for that purpose is defined and its general prin ciples are explained. It is demostrated how the composition of liquid and vapor phases can be calculated by using vapor pressure, partial pressure, equilibrium constant and relative volatility for binary systems. The chapters also includes information about the types of distillation and the distillation column used in the study. Than, in the light of these theoretical explanation, the distillation fusel oil is explained. The most important point is that, the dis tillation operation is at first carried out at laboratory scale and than the pilot-plant scale studies are realized in the light of re sults obtained from laboratory studies. Laboratory studies are very important in respect to planning of pilot-plant and industrial scale production and determining the amount of raw material and products on these scales. Laboratory studies on the distillation of the fu sel oil are divided into three sub groups: simple distillation, aze otropic distillation and distillation after removal of water. In the latter stage, the pilot-plant and industrial scale distillations of the fusel oil have theoretically been studied. The last section of this chapter includes the investigation of the other methods ex cept distillation used for fractionation of fusel oil. The studies of the esteri fi cation of alcohols of the fusel oil with acetic acid are presented in chapter five. This chapter starts with a section in which the realization of the esteri fication is ex plained and it is pointed out that esteri fication is an equilibrium reaction (reversible reaction). The important point in the esteri - fi cation process is to establish optimal operating conditions which result in a maximum yield without causing any hydrolysis reaction. Removal of water, the amount of excess reactants and catalyst have been reviewed as the major parameters affecting esteri fication react ions. The physical properties and the areas of use of the esters IX obtained by esteri fication are also studied in ttiis chapter. The aim of the esteri fication of the fusel oil is to separate alcohols and convert them into valuable products by esteri fication with ace tic acid. The products obtained by esterif icat ion can be used in more different areas and have higher economic value. The batch- scale and continuous esteri fication processes have also been studied in this section. The experimental studies and the results of analysis of the products obtained in the study are presented in chapter six. The studies are presented in a framework which includes information about the experimental set up and the experiments and given results of the analysis of products. Two fractions designated as fractions 2 and 3 obtained from the laboratory scale distillation of the fusel oil following remowal of water are consisted of 8.5% i-butyl alcohol and 91.5%i-amyl alcohol. This alcohols mixture makes up almost 65.0% of the original fusel oil and is the fraction which can be eva luated. However, the upper section of the heterogen phase of frac tion 1 does not contain any water. The percentage of i-amyl alcohol in this fraction is higher than 65%. Therefore, the useful fraction which can be extracted from the fusel oil reaches 86% by weight. The laboratory studies indicate that as the amount of benzene which used to remove water from the mixture increases the average production rate of product increases, production time of heterogene ous product does not change while the production time of homogeneous product and consequently the total product time decreases exponent ly. The total amount of heat used for distillation decreases and reaches an asimptotic value as the amount of benzene increase. However, dis tillation carried out with benzene can 10 % of energy and 20 % of time in comparison with distillation without benzene. But the addi tion of benzene to the fusel oil results in 3 % reduction in the distillation yield and the amount of benzene needed for the operation may be as high as 20 % of the fusel oil by volume in addition benzene may result in benzene pollution. In the pilot-plant experiments carried out at atmospheric pres sure 3.64 It heterogeneous phase (heavy fraction: 36.77 %, light fraction: 63.23 %), 11.2 It homogeneous fraction and 4.64 It bottom product is obtained from 19.4 It mixture. Seperation lasts 10.5 h. The percentage of i-amylalcohol may reach to 95.36 %, especially in the temperature distillation fractions. Here, it is important to carry out distillation with proper reflux ratio. But a 4.64 It bot tom product seems considerable large in comparison with results of the laboratory scale operation. This indicates that some alcohols which may be recovar able still remain in the bottom product. In order to recover alcohols remained in the bottom product pilot-plant distillation has also been carried out under vacuum conditions. In this case, 1 It heteregeneous phase, 15.1 It homoge neous phase and 4.5 It bottom product is obtained from a mixture of 20.6 It and seperation is ended in 110 minutes. Percentage of i- amyl alcohol of the high temperature fractions reaches to about 98.69 %. Another set of experimental studies is pilot-plant esterifica- tion of alcohols of fusel oil with acetic acid by reactive distilla tion method. In these experiments the fraction which is obtain from the fusel oil by distillation and has a high i-amyl alcohol content is used as a raw material for esteri fi cation. The informantion about the column used for esteri fi cation is given in previous chapter. The parameters which should be taken into consideration for the establish ment of optimum operating conditions are determined and their influ ence on the operation has been studied. A set of experiments is carried out to investigate the reboiler temperature as a pre-parameter. A maximum heating rate is obtained with 2.5 kW energy input for reboilers of 20, 18, 16, 12 and 10 It volumes. But higher energy input may heat vapor phase and result in a vigorous boiling. For that reason the energy input is kept fixed at 2 kW value. To investigate the influence of the reflux ratio as a pre-para meter experiment are done with total reflux and a reflux ratio = 1. In this case of the total reflux, reboiler and the column reaches a steady state temperature in 40 and 80 minutes, respectively, after heating starts. In the experiments carried out with a reflux ratio=l, the system does not reach a steady state temperature even in 60 minutes and the reboiler needs to be charged with raw material in order to compansale mass deplation due to fast vaporization. Study of the temperature history of the reboiler shows that a steady state heat balance can be established in a longer period, by increa sing reflux ratio and under these condition the fluid in the reboiler does not rapidly delete. A volume alcohol mixture/acid=2 ratio is found to be value pro viding a proper starting concentration since no acid is determined in the mixture after esteri f i cation completed. Therefore, it is seen possible to esteri ficate the acid completely with excess alco hol. A feeding stream with the same alcohol mixture/acid ratio pro vides proper conditions for a smooth operation. Since the experimental set up does not have any preheating system, the cold raw material is fed to the plate 1 of the column in order to heat it up to the average column temperature. It is clear that the feeding of the material to the plates in upper section of the column can seriously disrupt the steadiness of the column operation and it needs a longer time to reach a steady state opera tion. H2SO4 which is used as an acidic catalyst: in the experiments, enhanced the esteri fi cation reaction and absorbed the water in the system. xi During the pilot-plant esterification of alcohols of the fusel oil with acetic acid the investigation of feeding flow rate which is an operation parameter, has been done with a alcohol mixture/acetic acid=2. It is observed that as the flow rate increases the time needed to reach steady state operating temperature decreases. But when the feed flow rate is too high, such as in the case of alcohol mixture/acid=2.5/1.25, accumulation of liquid in the reboiler is not fast enoungh consequently the heating scale exceeds vaporization rate of the liquid which prevents vapor to reach the upper section of the column. Therefore, it is necessary to change the reflux ratio. The amyl alcohol percentage in the top product of distilla tion carried out with alcohol mixture/acid=1.5/0.75 and 2.5/1.25 is about 11.0 and 12.5 respectively. The percentage of n-propyl alco hol in top product in the lader case is 5. These results show that hydrolysis occurs in the of equilibrium reactions and it may reach 17.7 % in the top product. The bottom products of both distillation operations contain 21.0 % n-propyl alcohol and i-amyl alcohol. Column of pilot-plant esterification of alcohols of fusel oil with acetic acid by reactive distillation method is shown in Figure. xn Acid Feed Tank Condenser Flowmeter - Y- Condensed Tank Reflux Divider Vapor Sample Liquid Sample Top Product Tank Acid Feed Line Dozage Pump Reboiler Heater Alcohol Feed Tank Alcohol Feed Line Temperature Panel Termostat Heat Regulater Bottom Products Figure-] Esteri fi cation Column.
Determination of optimum operation conditions in the process of the production of acetic esters from the fusel oil alcohols
Tez (Doktora)-- İTÜ Fen Bil.Enst., 1993
Keywords: Asetik esterler; Fuzel yağı; Acetic esters; Fusel oil